Implementation of computing with words in evaluating training program (2015)
The decision-making problems have attracted the attention of many researchers in a wide range of disciplines. The decision situations in which multiple individuals involved, each with their own knowledge about alternatives of the decision problem requires advanced to deal with this difficulty techniques. This work evaluates the impact of training received by a group of workers in the assessments are modeled using different kinds of information provided by different groups of experts to manage the uncertainty and subjectivity of such assessments for there to infer its relationship with the training received. Therefore, it is necessary and appropriate to establish a framework adapted to the heterogeneous nature of these criteria. Model and manage uncertainty has been successful and involves making computing processes with words hence the model 2-tuples linguistic representation is offered as a solution for their accuracy, ease of information management in complex frameworks, as to give greater interpretability of the resulting data.